Letter Of Credit (L/C) Dalam Perspektif Pemikiran Abdul Mannan - Muhammad Nabhani; Bustanul Arifin (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background. Given the existence of legal provisions regarding the implementation of L/C transactions, it is hoped that L/C will run smoother and increase so that it has a positive impact on the growth of international trade. PBI L/C provisions are made in line with UCP 500 provisions and international L/C law so that the material for PBI L/C is on an international scale. PBI L/C will not hamper L/C practices that have been carried out by banks and the business world so far. PBI L/C actually legally covers the practice of L/C.Aim. From the presentation of the above, it will give rise to a number of problems that need to be solved. First: what is the perspective of Islamic law regarding the implementation of L/C based on the concept of Sharia? .Second: how does Abdul Mannan give his theoretical concept of the existence of L/C which is a service product in Sharia banking? This problem requires solving through a historical-philosophical approach.Methods. In this study, the authors used a qualitative approach in research procedures to produce holistic-descriptive data from the observed phenomena. The reason for choosing this qualitative method is to obtain a comprehensive description related to perceptions, actions, normative legal force and Islamic law which enforces L/C as a means of international payment that has developed to date.Results. L/C syari'ah plays an important role in the international payment system when compared to other payment systems. The existence of the application of shari'ah contracts included in the implementation of the shari'ah L/C implies the importance of the position of shari'ah L/C compared to conventional L/C. Thus, even though Mannan's opinion has not been fully implemented in Indonesia, Mannan's thoughts can be used as a comparative study against other models of economic systems.